Animal Protection System Cats and Dogs Approaching The Substance With The Mini Computer - Aulia Ramadhani, Shafira; Anandika, Arrya; Syahputra, Ronaldo; Purbolingga, Yoan (Universitas Andalas, 2025)
Litter bins that do not have lids, as well as the time span of garbage collection, especially when garbage is accumulating, can attract animals to enter the bin, some of the animal patterns are to carry garbage out of the bin, so that it can be consumed by dogs/cats. The purpose of this problem is to help the community in preventing and minimizing animals that litter and prevent the spread of diseases in animals due to consuming garbage, for example diseases caused by bacteria from garbage, namely rabies. This final project results in the detection of cats and dogs using YOLO with 90% accuracy, when a cat or dog is detected the system will issue an output so that the animal does not get closer and out of the trash, the output will continue to be issued until the animal is no longer detected by the camera.